2000
DOI: 10.1152/ajpcell.2000.279.6.c1859
|View full text |Cite
|
Sign up to set email alerts
|

15-Deoxy-Δ12,14-prostaglandin J2facilitates thyroglobulin production by cultured human thyrocytes

Abstract: A cyclopentenone-type prostaglandin, 15-deoxy-Delta(12, 14)-prostaglandin J(2) (15-d-PGJ(2)), has been shown to induce the cellular stress response and to be a ligand for the peroxisome proliferator-activated receptor (PPAR)-gamma. We studied its effect on the basal and thyrotropin (TSH)-induced production of thyroglobulin (TG) by human thyrocytes cultured in the presence of 10% FBS. In 15-d-PGJ(2)-treated cells in which the agent itself did not stimulate cAMP production, both the basal production of TG and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…In the present article, we demonstrated that this effect of 15d-PGJ 2 is not mediated by HO-1 activation. Similarly, Kasai et al showed that the upregulation of HO-1 was not involved in the augmentation of thyroglobulin production in 15d-PGJ 2 -treated thyrocytes (20). Thus, HO-1 is not a general mediator of 15d-PGJ 2 activities, but seems to be involved only in some of them.…”
Section: Discussionmentioning
confidence: 97%
“…In the present article, we demonstrated that this effect of 15d-PGJ 2 is not mediated by HO-1 activation. Similarly, Kasai et al showed that the upregulation of HO-1 was not involved in the augmentation of thyroglobulin production in 15d-PGJ 2 -treated thyrocytes (20). Thus, HO-1 is not a general mediator of 15d-PGJ 2 activities, but seems to be involved only in some of them.…”
Section: Discussionmentioning
confidence: 97%
“…However, other results also suggest the involvement of PUFA n-6 in the stimulation of thyroid activity. The endogenous ligand of peroxisome proliferator activated receptor γ (PPARγ) -15-deoxy-Δ 12,14 -PGJ 2 (15d PGJ 2 ) -a product of C20:4 metabolism (Forman et al, 1995) was shown to facilitate the synthesis of thyroglobulin in a functional rat epithelial cell line (Kasai et al, 2000). Taking into consideration the similar mode of regulation of thyroglobulin and TPO gene transcription (Espinoza et al, 2001), 15dPGJ 2 might represent an intermediate in the signalling pathway by which PUFA affect TPO level.…”
Section: Discussionmentioning
confidence: 99%
“…Robbins and colleagues showed that ␥-linolenic acid and 15dPGJ 2 increase the expression of catalase and other antioxidant enzymes in normal astrocytes, but not in glioma cells (68) (unpublished observations). In addition, 15dPGJ 2 induces expression of heme oxygenase-1 (22), which is cyto-protective at low levels while higher expression levels are cyto-toxic (69)(70)(71).…”
Section: Discussionmentioning
confidence: 99%